2004
DOI: 10.5194/angeo-22-2775-2004
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric conductivity dependence of dayside region-0, 1, and 2 field-aligned current systems: statistical study with DMSP-F7

Abstract: Abstract. The present study statistically examines the dependence of the intensities of dayside (MLT=8-12 h) large-scale field-aligned currents (FACs) on the ionospheric conductance using the summary data of DMSP-F7 constructed by the procedure of Higuchi and Ohtani (2000). We have found that, in the dayside region, R1 and R0 have a higher correlation between ionospheric conductivity and FAC intensity than R2, suggesting that R0 and R1 are driven by a more voltage-like source than R2. This result is consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 20 publications
6
31
0
Order By: Relevance
“…The R1 (R2) FAC flows into the poleward (equatorward) boundary of auroral latitudes in midnight-noon (noon-midnight) sector centered around dawn (dusk) and flowing out of auroral ionosphere in noon-midnight (midnight-noon) sector centered around dusk (dawn). Coming to the interhemispheric asymmetry as observed in the present study, recent investigations on seasonal dependence of FACs have highlighted prominent differences accounting up to 2-3 times higher magnetic activity in summer (sunlit) than winter (dark) hemisphere although the conductivity in winter hemisphere could be one-tenth of the summer hemisphere (Haraguchi et al, 2004;Mishin et al, 2016). The current density and resulting ionospheric DP2 Hall currents and Pedersen currents due to each of the R0, R1, and R2 currents is highly specific for a given local time be it day or night (Haraguchi et al, 2004).…”
Section: Journal Of Geophysical Research: Space Physicssupporting
confidence: 68%
See 1 more Smart Citation
“…The R1 (R2) FAC flows into the poleward (equatorward) boundary of auroral latitudes in midnight-noon (noon-midnight) sector centered around dawn (dusk) and flowing out of auroral ionosphere in noon-midnight (midnight-noon) sector centered around dusk (dawn). Coming to the interhemispheric asymmetry as observed in the present study, recent investigations on seasonal dependence of FACs have highlighted prominent differences accounting up to 2-3 times higher magnetic activity in summer (sunlit) than winter (dark) hemisphere although the conductivity in winter hemisphere could be one-tenth of the summer hemisphere (Haraguchi et al, 2004;Mishin et al, 2016). The current density and resulting ionospheric DP2 Hall currents and Pedersen currents due to each of the R0, R1, and R2 currents is highly specific for a given local time be it day or night (Haraguchi et al, 2004).…”
Section: Journal Of Geophysical Research: Space Physicssupporting
confidence: 68%
“…This brings to the simulation studies (e.g., Huang, Foster, & Kelley, 2005;Huba et al, 2005;Maruyama et al, 2005 andPeymirat et al, 2000) of under (over) shielding conditions and its relation with equatorial E × B drifts (Huang, 2015(Huang, , 2019 wherein imbalance between R1 and R2 currents has been shown as shape function of southward (northward) IMF Bz or more effectively as a step or linear shape function of PC potential. Thus, the effectiveness of either under and over shielding conditions at a time largely depends on response of R1 and R2 currents and its effect on PC potential drop as well as auroral electrojet variations (Haraguchi et al, 2004;Moon, 2012;Pulkkinen et al, 2016;Myllys et al, 2016). Thus, the effectiveness of either under and over shielding conditions at a time largely depends on response of R1 and R2 currents and its effect on PC potential drop as well as auroral electrojet variations (Haraguchi et al, 2004;Moon, 2012;Pulkkinen et al, 2016;Myllys et al, 2016).…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…On the dayside the large-scale field-aligned currents (FACs), Region 1 (R1) and Region 2 (R2) currents, are noticeably stronger (i.e., the FAC density is larger) and more intense (i.e., the FAC intensity is larger) in the summer/sunlit hemisphere than in winter/dark hemisphere (e.g., Coxon et al, 2016;Fujii et al, 1981;Haraguchi et al, 2004;Ohtani, Ueno, Higuchi, & Kawano, 2005;Wang et al, 2005), which can be attributed to the higher ionospheric conductance of the summer/sunlit hemisphere due to solar extreme ultraviolet (EUV) radiation. On the dayside the large-scale field-aligned currents (FACs), Region 1 (R1) and Region 2 (R2) currents, are noticeably stronger (i.e., the FAC density is larger) and more intense (i.e., the FAC intensity is larger) in the summer/sunlit hemisphere than in winter/dark hemisphere (e.g., Coxon et al, 2016;Fujii et al, 1981;Haraguchi et al, 2004;Ohtani, Ueno, Higuchi, & Kawano, 2005;Wang et al, 2005), which can be attributed to the higher ionospheric conductance of the summer/sunlit hemisphere due to solar extreme ultraviolet (EUV) radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of a voltagedriven current is proportional to the ionospheric Pedersen conductivity s P but that of the currentdriven current is not. Recently, Haraguchi et al (2004) investigated the correlation between the ionospheric conductivity and the FAC intensity in the dayside region using DMSP-F7 magnetometer data. These authors concluded that R0/R1 is associated with a voltage-like source and R2 is associated with a more current-like source.…”
Section: Article In Pressmentioning
confidence: 99%